Development of Higher Order Thinking Skills (HOTS) Test Items in IPAS to Evaluate Fifth-Grade Students’ Problem-Solving Abilities - Juita, Marselina; Lastuti, Sri; Hairunisa, Hairunisa (Journal of Educational Sciences, 2025)
Higher Order Thinking Skills refer to advanced cognitive abilities involving analysis, evaluation, and creation in solving problems critically and logically. Problem-solving skills are defined as an individual’s ability to identify problems, formulate alternative solutions, and evaluate outcomes systematically. This study aims to develop a test instrument based on higher order thinking skills for the Natural and Social Sciences subject for fifth-grade elementary students that is valid and reliable in measuring problem-solving skills. The research employed a research and development method using a modified Borg and Gall model consisting of seven stages. The developed instrument consists of 25 multiple-choice items. Content validity, assessed using Aiken’s V formula, obtained a score of 0.81, indicating a very valid category. Construct validity showed that 16 out of 25 items were valid after revision. Reliability testing using the split-half technique produced coefficients of Cronbach’s Alpha, Spearman-Brown, and Guttman above 0.98, indicating strong internal consistency. The difficulty index ranged from 0.42 to 0.51 (moderate), while the discrimination index showed that 16 items had values equal to or greater than 0.755. The instrument is considered valid and feasible for use.